Occupational Exposure to Inhalation Anesthetics in Operating Room and Adverse Health Outcomes: A Systematic Review - Caronna, Andrea; Vitale, Katia; Ciccariello, Laura; De Giorgi, Andrea; Gazzanelli, Sergio; Ricci, Lidia; Vitali, Matteo; Protano, Carmela (La Medicina del Lavoro, 2026)
Summary: Volatile anesthetics (VA) are essential agents for inducing and maintaining unconsciousness during specific surgical procedures, but they pose several health risks for exposed workers. The aim of the systematic review was to assess the effects of long-term VA occupational exposure in operating rooms. The review was conducted in accordance with the PRISMA Statement, and the search was conducted in PubMed, Scopus, and Web of Science to identify articles published between January 1, 1994, and December 31, 2024, that reported data from observational, quasi-experimental, and experimental studies. The protocol was registered in PROSPERO (ID: CRD42024500838). The quality of the studies was assessed using the standard Newcastle-Ottawa Scale versions for cohort and case–control studies, and an adapted version for cross-sectional studies. A total of 65 studies were included. Adverse effects were categorized into four groups: reproductive and Adverse pregnancy or offspring outcomes, neurotoxic alterations, laboratory parameter changes, and cyto- and genotoxicity. Overall, no significant associations were found between VA exposure and reproductive or pregnancy outcomes. One study reported neurological alterations (prolonged reaction times). Additionally, some studies have documented impairments in immune function and minor alterations in renal and hepatic function parameters. Finally, several studies indicated an increased risk of genotoxicity and oxidative stress. Given this evidence, protective measures and health surveillance for exposed workers remain crucial preventive measures.